Land alienation restoration in tribal communities in India (Bombay, 1977)
The book brings together papers read in a National Seminar on Land Alienation and Restoration in Tribal Areas in India, held in June 1976, at the Tata Institute of Social Sciences, Bombay. The participants to the Seminar were the senior government officials from the States which have concentration of tribal population, from the office of the Director General of Backward Classes and the Commissioner for Scheduled Castes and Scheduled Tribes. The papers critically examine the development and contents of land poli cies in Andhra Pradesh, Maharashtra, Orissa, Bihar, Madhya Pradesh, Rajasthan and Gujarat which affect the tribals, identify reasons loopholes in the tenancy legislation, slackness in the implementation of legislative provisions and socio-econo mic conditions of the tribals -of land alientation, and examine the measures taken by the State Governments to prevent alienation and to restore the alienated land. The authors objectively and comprehensively analyse administrative issues involved in the implementation of land policies in tribal areas. The book contains pragmatic and creative suggestions to deal with the problem of land alienation among tribals Policy makers as well as field workers will find this comprehensive and perceptive analysis by very experienced administrators extremely useful freshing.
Keywords: India-Tribes and tribal system